An Arctic Science Policy? All We Need is a Sovereignty Crisis - Pyc, Cynthia (ARCTIC, 2000)
. The general consensus appears to be that the Canadian government has lost interest in the Arctic. However we need only to examine our history to see that Canadians, and the government as their representative, have never really been interested in Arctic science and research - that is, unless our Arctic sovereignty seemed to be threatened by a competing interest. . What policy exists in regard to Canada's polar regions has evolved out of . knee-jerk reactions. . Throughout the 1990s, with Arctic sovereignty no longer a hot issue, the government has gone silent on the issue of polar research, pausing once to create the Canadian Polar Commission, and then subsequently cutting the budgets of departments and institutions that support the discovery of polar knowledge. As we enter the 21st century, we will undoubtedly be faced with future perceived encroachments of foreign actors on Canadian soil. Is it true that Canada's effective occupation of the Arctic will diminish with increasing foreign activity there? Can we consider the actions on Axel Heiberg last summer sufficient threat to Canadian sovereignty? If this is the case, then can we expect government, urged on by polar scientists, to respond with an Arctic science policy? . The only thing that will bring the Arctic back to Canada is not a quick-fix patch, but a concerted effort to mend the relationship through an integrated national science policy with an associated strategic plan, and a strategy for polar science as a component of that plan.